The Covid-19 lesson from Sweden: Don't lockdown - Fredrik N. G. Andersson; Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2023)
The coronavirus pandemic triggered strong political action across Europe. Mandatory restrictions to increase social distancing were imposed, commonly known as lockdowns. In some cases, entire countries were virtually locked down for several weeks at a time, contributing to a very severe downturn in economic activity. To mitigate the policy induced economic crisis, governments responded by introducing expansionary fiscal and monetary measures to support businesses and households. One country, Sweden, served as an outlier. It restricted the spread of the virus primarily through voluntary measures rather than strict lockdowns. In this study, we compare the health and economic outcomes in Sweden with those of comparable Western European countries. We answer the question of whether the Swedish policy of using voluntary social-distancing measures led to a better or worse outcome compared to those countries relying on extensive lockdowns. Our results clearly show that the benefits of the lockdown policy on the excess death rate was at best limited, while the economic costs were significant. The Swedish policy of advice and trust in the population to act responsibly was relatively successful. Unlike most other Western European countries, Sweden managed to combine one of the lowest excess death rates with relatively small economic costs. Furthermore, Sweden's fiscal position remained remarkably strong during and after the pandemic, in sharp contrast to the fiscal deterioration in those countries that pursued more stringent lockdown policies. While we make no claims of presenting a comprehensive study that covers all possible dimensions of a complex question, the macroeconomic outcome suggests an overreaction, if not panic, among policymakers in many Western European countries. Future policymakers should rely on empirical evidence instead of panicking and adopting extreme measures. The panicked implementation of strict measures during the pandemic did far more harm than good-even if policymakers were appearing to act in a decisive and rapid way for the best interests of society.
Keywords: E58; E65; F43; H51; H63; I10; N14; 330; Covid-19 pandemic; lockdowns; excess mortality; economic crisis; fiscal policy; monetary policy; ECB; public debt